2022
DOI: 10.3389/fpls.2022.1067713
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 concentration induces changes in plant growth, transcriptome, and antioxidant activity in fennel (Foeniculum vulgare Mill.)

Abstract: IntroductionFennel (Foeniculum vulgare Mill.) is widely used to produce natural bio-materials. Elevated CO2 (eCO2) concentrations in the atmosphere improve the net photosynthesis of plants.MethodsThe aim of the present study was to investigate distinct changes in fennel growth characteristics and phytonutrient contents under different CO2 concentrations. The effects of 400 and 800 ppm concentrations on plant growth and antioxidant activity were observed under hydroponics.Results and DiscussionPlant growth was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…The top part of forage maize was used to evaluate the antioxidant activities of plants in the different fertilizer-treated groups. The total phenol and flavonoid contents, nitrate-scavenging activities, reducing power, and ABTS were determined as described previously ( Jo et al., 2022 ). All measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The top part of forage maize was used to evaluate the antioxidant activities of plants in the different fertilizer-treated groups. The total phenol and flavonoid contents, nitrate-scavenging activities, reducing power, and ABTS were determined as described previously ( Jo et al., 2022 ). All measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Plants can keep their photosynthetic rates high while maintaining a relatively low level of stomatal conductance even when CO 2 concentrations rise [10,11]. Previous studies showed that flavonoid content increases under elevated carbon dioxide conditions, while antioxidant activity, including total phenolic content, decreases [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…총 플라보 노이드 함량(TFC)을 분석하기 위하여 케르세틴(Quercetin, Sigma-Aldrich, ) 510 nm의 파장을 이용하여 표준곡선을 작성하였다 (Zhishen et al,1999). 실험 방법은 각각 자유 라디칼 소거활성(DPPH scavenging activity)은 (Brand-Williams et al, 1995), 질산염 소거 활성(Nitrite scavenging activity)은 (Kao et al, 2011), 환원력 분석(Reducing power)은 (Oyaizu, 1986), ABTS 라디칼소거활성은 (Re et al, 1999)의 방법을 일부 수정하여 이용되었다 (Jo et al, 2022). 각 항산화 활성 실험을 위한 표준물질의 정량곡선은 0.99 이상의 적절한 결정계수(R 2 )를 나타내었다(Figure 1).…”
unclassified